IgA Nephropathy in Salvador, Brazil. Clinical and laboratory presentation at diagnosis - Souza,Brenda Navarro de (2018)
ABSTRACT Introduction: IgA nephropathy (IgAN) is the most prevalent primary glomerulopathy in the world, but great variation is reported in different countries. In Brazil, the reported prevalence is high in the Southeastern States and low in Salvador, Bahia State, Brazil. Objectives: This study investigated the clinical and histological patterns of patients with IgAN in Salvador, Brazil. Methods: This is a descriptive study that included all patients with a diagnosis of IgAN performed in native kidney biopsies collected from referral nephrology services of public hospitals in Salvador between 2010 and 2015. Results: Thirty-two cases of IgAN were identified, corresponding to 6% of primary glomerulopathies. There was a slight male predominance (56%) and the median age was 30 [22-40] years. Hematuria was present in 79%, non-nephrotic proteinuria was present in 61%, and hypertension was present in 69% of patients. Segmental sclerosis (S1 lesions) was present in 81% of cases, and chronic tubulo-interstitial lesions (T1 and T2 lesions) were present in 44% of cases. Patients with M1 and T2 MEST-C scores exhibited higher serum urea and creatinine than other patients. Conclusion: The prevalence of IgAN was lower in Salvador than other regions of Brazil. Chronic histological lesions and laboratory markers of severe disease were frequent. M1 and T2 MEST-C scores were correlated with markers of renal dysfunction.